Peran Mediasi Human Capital dan Kinerja Individu dalam Hubungan Praktek MSDM dengan Kinerja Organisasi - Jonner Simarmata (Universitas Batanghari, 2021)
This research aims to investigate the role of HC mediation and individual performance in the relationship of MSDM practice with organizational performance in the context of IMK. To achieve this goal, a set of questionnaires was distributed to 300 respondents. They consist of 40 entrepreneurs and 260 craftsmen selected with multi-stage random sampling techniques. The collected data is analyzed by the SEM-PLS method. Data analysis results in that (1) MSDM practices have a positive and significant effect on HC, individual performance, and organizational performance, (2) HC and individual performance mediate the relationship of MSDM practice with organizational performance. The findings of this study have implications for the theory that the relationship of MSDM practice with organizational performance is increasingly clarified. This finding suggests that IMK actors, especially those engaged in the Jambi batik industry, to further streamline HC development and improve individual performance through more effective MSDM practices to achieve more effective organizational goals.